Dysfunctional posttraumatic cognitions, posttraumatic stress and depression in children and adolescents exposed to trauma: a network analysis. (7th November 2019) - de Haan, Anke; Landolt, Markus A.; Fried, Eiko I.; Kleinke, Kristian; Alisic, Eva; Bryant, Richard; Salmon, Karen; Chen, Sue‐Huei; Liu, Shu‐Tsen; Dalgleish, Tim; McKinnon, Anna; Alberici, Alice; et al.
Abstract : Background: The latest version of the International Classification of Diseases (ICD‐11) proposes a posttraumatic stress disorder (PTSD) diagnosis reduced to its core symptoms within the symptom clusters re‐experiencing, avoidance and hyperarousal. Since children and adolescents often show a variety of internalizing and externalizing symptoms in the aftermath of traumatic events, the question arises whether such a conceptualization of the PTSD diagnosis is supported in children and adolescents. Furthermore, although dysfunctional posttraumatic cognitions (PTCs) appear to play an important role in the development and persistence of PTSD in children and adolescents, their function within diagnostic frameworks requires clarification. Methods: We compiled a large international data set of 2, 313 children and adolescents aged 6 to 18 years exposed to trauma and calculated a network model including dysfunctional PTCs, PTSD core symptoms and depression symptoms. Central items and relations between constructs were investigated. Results: The PTSD re‐experiencing symptoms strong or overwhelming emotions and strong physical sensations and the depression symptom difficulty concentrating emerged as most central. Items from the same construct were more strongly connected with each other than with items from the other constructs. Dysfunctional PTCs were not more strongly connected to core PTSD symptoms than to depression symptoms. Conclusions: Our findings provide support that a PTSD diagnosis reduced to its core symptoms could help to disentangle PTSD, depression and dysfunctional PTCs. Using longitudinal data and complementing between‐subject with within‐subject analyses might provide further insight into the relationship between dysfunctional PTCs, PTSD and depression.